Perinatal outcomes and sinopharm BBIBP-CorV vaccination during pregnancy - Donya Hatami; Abbas Habibelahi; Nasrin Changizi; Mohammad Heidarzadeh; Marzieh Nojomi; Moein Rast; Kiarash Ansari; Arash Tehrani‐Banihashemi (BMC, 2024)
Abstract Background After the outbreak of COVID-19, a huge part of the health care services was dedicated to preventing and treating this disease. In case of COVID-19 infection, severe COVID-19 is reported more in pregnant individuals. Afterward, Vaccination against SARS-CoV-2 became a hot topic due to known effects in preventing severe COVID-19 during pregnancy. Vaccination of pregnant individuals started in August 2021 with the Sinopharm vaccine in Iran. The aim of current study was to determine the incidence of perinatal outcomes in women who were vaccinated during pregnancy. Method This retrospective cohort study included 129,488 singleton births from March 21, 2021, until March 21, 2022, in Tehran, Iran. The data was obtained from the Iranian Maternal and Neonatal (IMaN) Network and the Maternal Vaccination Registry. Adverse perinatal outcomes investigated in this study include preterm birth, extremely preterm birth, low birth weight, very low birth weight, intrauterine growth restriction, stillbirth, neonatal intensive care unit admission, congenital anomaly, neonatal death and low 5-minute Apgar score. The risk of all perinatal outcomes was evaluated using multiple logistic regression. The analysis was done using STATA version 14. Results Of all 129,488 singleton births included in this study, 17,485 (13.5%) were vaccinated against SARS-CoV-2 (all with Sinopharm (BBIBP-CorV)). The exposure to the Sinopharm vaccine during pregnancy caused a significant decrease in the incidence of preterm birth (P =0.006, OR=0.91 [95% CI, 0.85 to 0.97]), extremely preterm birth (P =<0.001,OR=0.55 [95% CI, 0.45 to 0.66]), and stillbirth (P =<0.001, OR=0.60 [95% CI, 0.47 to 0.76]). Exposure to vaccination during the first trimester was associated with an increased risk of preterm birth (P =0.01, OR=1.27 [95% CI, 1.04 to 1.55]) Maternal vaccination during pregnancy was not associated with an increased risk of other adverse perinatal outcomes included in this study. Conclusion The finding of this population-based study indicated no adverse pregnancy outcome due to vaccination with the Sinopharm vaccine during the second and third trimesters of pregnancy. Overall risk of adverse pregnancy outcomes were lower in the vaccinated individuals compared to the unvaccinated group. Also, vaccination during the first trimester was associated with an increased risk of preterm birth.